Eliberarea ordonanţei judecătoreşti în temeiul pretenţiei ce rezultă din nerestituirea cărţilor împrumutate de la bibliotecă - Creţu, Vasile; Josanu, Ilona (CEP USM, 2024)
În this article the authors analyse the civil procedural conditions for the release of the court order on the basis of the claim resulting from the non-return of books borrowed from the library. The authors follow the goal to state the material-procedural conditions for the release of the court order in these cases examined based on the claim filed by the creditor under the writ proceedings, state the documents which will be necessary to be attached by the creditor to his/her claim as well as debate on types of claims which cannot be filed by the creditor on this basis under the writ proceedings. Following the performed analyses through applied synthesis, deduction and compared analyses of the national normative framework, the authors propose amendments to letter h) of Art. 345 of the Civil procedure code of the Republic of Moldova.
RELEASE OF THE COURT ORDER ON THE BASIS OF THE CLAIM RESULTING FROM THE NON-RETURN OF BOOKS BORROWED FROM THE LIBRARY
Keywords: Court; Court order; creditor; debitor; writ proceedings